Red-mud-based multi-solid-waste water stabilizing material with improved weather resistance and preparation method of red-mud-based multi-solid-waste water stabilizing material
By using a hyperbranched epoxy resin emulsion prepared by multi-arm polyethylene glycol thiol and monoalkenyl epoxy compounds in the water-stabilizing layer material, the problem of discontinuous bonding of industrial solid waste in the water-stabilizing layer material is solved, the material's weather resistance and service life are improved, and the efficient reuse of industrial solid waste is achieved.
Patent Information
- Application Number
- CN202411945558.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The application of existing industrial solid waste in water-stabilizing layer materials has problems such as excessive pores, incomplete hydration, and discontinuous bonding, which leads to cracking between the aggregate and the industrial solid waste gelling material under the action of water-salt/freeze-thaw cycle, reducing the durability of the water-stabilizing layer.
The hyperbranched epoxy resin emulsion prepared by reaction of multi-arm polyethylene glycol thiol and monoalkenyl epoxy compounds through Michael addition is used to enhance the binding force between the aggregate and the gelling material, form a stable chemical bond, and improve the weather resistance of the water-stable material.
It effectively reduces the risk of cracking between aggregate and industrial solid waste gelling materials under the water-salt/freeze-thaw cycle, extends the service life of water-stabilizing materials, and realizes the comprehensive reuse of industrial solid waste resources, reducing the cost of road projects.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solid waste recycling, and specifically relates to a red mud-based multi-solid waste water-stabilizing material with improved weather resistance and a preparation method thereof. Background Art
[0002] The water-stabilizing layer is an important structural layer between the bottom layer and the surface layer of the highway, and plays a decisive role in the overall performance of the highway. The water-stabilizing layer usually uses cement-stabilized aggregate or lime-stabilized aggregate as the main base material. The construction process involves mixing stones and stabilizers (such as cement or lime) according to the specified ratio, then adding water for stirring, and then paving and compacting to form a layer of structure with certain strength and stability. The main purpose of designing the water-stabilizing layer is to improve the load-bearing performance of the pavement structure and its resistance to deformation, and to ensure that the asphalt or concrete surface layer can be supported by a stable and reliable foundation. However, with the rapid development of highway construction, the consumption of materials such as sand and gravel, cement, etc. is large, and the raw material regeneration capacity of these materials is poor. Therefore, it is urgent to seek low-priced, large-supply and safe materials to replace sand and gravel and cement to solve the problem of resource shortage.
[0003] Industrial solid wastes such as red mud, fly ash, and slag are discharged every day. At present, the resource utilization technology for such solid wastes is not mature enough and cannot be reused in large quantities. The main disposal method is accumulation and burial, which causes waste of land resources. Resource utilization is the best way to dispose of industrial solid wastes, especially in roadbed water-stabilizing materials, which can realize the large-scale disposal of industrial solid wastes and significantly improve the comprehensive utilization level of industrial solid wastes. For example, patent CN101671986B discloses a road material produced using Bayer red mud, comprising a road base, a road water-stabilizing layer and a road surface layer, wherein the road base is made of the following raw materials in weight percentage: 4-25% low-temperature ceramic curing agent, 45-96% red mud and 0-30% aggregate, the road water-stabilizing layer is made of the following raw materials in weight percentage: 8-20% low-temperature ceramic curing agent, 10-20% red mud and 60-82% aggregate, and the road surface layer is made of the following raw materials in weight percentage: 10-30% low-temperature ceramic curing agent, 2-10% red mud and 60-88% aggregate. Patent CN113698164B discloses a road water-stabilizing layer material for crack prevention and subsidence and a preparation method thereof, wherein the raw materials include gypsum cementitious material, aggregate, and water; the gypsum cementitious material includes a main material and a construction admixture, wherein the main material includes building gypsum, slag powder, silica fume, cement, and fly ash; the construction admixture includes a water reducer, a retarder, hydroxypropyl methylcellulose, and an air entraining agent. Patent CN110423085B discloses a road water-stabilizing layer material for crack prevention containing electrolytic manganese slag and a preparation method thereof, wherein the water-stabilizing layer material includes the following raw materials in parts by weight: 100 parts of electrolytic manganese slag, 40-60 parts of red mud, and 5-10 parts of a composite phase change material, wherein the phase change composite material is formed by compounding a phase change material and expanded graphite and then coating with an organic resin.
[0004] The above is a technology that uses industrial solid waste to replace cement and sand and gravel, thereby minimizing the use of cement and sand and gravel, and effectively improving the recycling rate of industrial solid waste. It can not only reduce the overall cost of the project, but also meet the current construction standards. However, due to the irregular shape, impurities, low activity and high proportion of aggregate in the water-stabilizing layer of industrial solid waste, the bonding interface between industrial solid waste and aggregate is not as close and continuous as cement and aggregate. There are defects such as large pores, incomplete hydration, and discontinuous bonding. Although it will not have a significant impact on the compressive strength of the overall water-stabilizing material, cracks will occur between the aggregate and the industrial solid waste cementitious material under the action of water-salt / freeze-thaw cycles, which significantly reduces the durability of the water-stabilizing layer.
[0005] Therefore, it is necessary to develop a water-stable material with excellent resistance to water-salt / freeze-thaw cycles to expand its application in areas covered by frozen and saline soils. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a red mud-based multi-solid waste water-stabilizing layer material with improved weather resistance and a preparation method thereof. The raw materials of the water-stabilizing material include a hyperbranched epoxy resin emulsion prepared by Michael addition reaction of multi-arm polyethylene glycol thiol and monoolefin epoxy compounds. The terminal epoxy functional group density of the hyperbranched epoxy resin is high, and a large number of terminal epoxy groups can chemically react with active groups on the surface of aggregates and cementitious materials to form stable chemical bonds, thereby enhancing the bonding force between aggregates and cementitious materials, reducing the risk of cracking between aggregates and industrial solid waste cementitious materials under the action of water-salt / freeze-thaw cycles, and extending the service life of the water-stabilizing material.
[0007] In order to achieve the above purpose, the following technical solutions are adopted:
[0008] A red mud-based multi-solid waste water-stabilizing material with improved weather resistance comprises the following raw materials in parts by weight: 15-30 parts of Bayer red mud, 15-30 parts of fly ash, 2.5-4 parts of desulfurized ash, 3-5 parts of cement, 80-100 parts of aggregate, 30-40 parts of hyperbranched epoxy resin emulsion, 1-3 parts of alcoholamine early strength agent, and 5-15 parts of water; the hyperbranched epoxy resin emulsion is prepared by Michael addition reaction of multi-arm polyethylene glycol thiol and monoolefin epoxy compounds at a molar ratio of thiol to olefin of 1:1-1.1.
[0009] The multi-arm polyethylene glycol thiol has a weight average molecular weight of 10,000 to 30,000 and is selected from one or a combination of two or more of four-arm polyethylene glycol thiol, six-arm polyethylene glycol thiol, and eight-arm polyethylene glycol thiol, preferably eight-arm polyethylene glycol thiol.
[0010] The monoolefin epoxy compound is selected from one or a combination of two or more of 3,4-epoxycyclohexyl methyl methacrylate, (3,4-epoxycyclohexyl) methyl acrylate, glycidyl acrylate, glycidyl methacrylate, and 4-hydroxybutyl acrylate glycidyl ether.
[0011] The hyperbranched epoxy resin emulsion has a solid content of 18-25%.
[0012] Specifically, the hyperbranched epoxy resin emulsion is prepared by a method comprising the following steps:
[0013] The multi-arm polyethylene glycol sulfur, the base catalyst and the organic solvent are uniformly mixed, and the monoolefin epoxy compound is added to control the temperature for reaction. After the reaction is completed, the organic solvent is evaporated, and water is added, and shearing and stirring are performed to obtain a hyperbranched epoxy resin emulsion.
[0014] Hyperbranched epoxy resin is a polyether-type hyperbranched epoxy resin with a terminal epoxy group and a hydrophilic polyether skeleton structure, which is prepared by the Michael addition reaction of multi-arm polyethylene glycol thiol and monoolefin epoxy compounds. The hydrophilic polyether skeleton and hydrophobic terminal epoxy groups make the hyperbranched epoxy resin self-emulsifying and can be spontaneously dispersed into a stable emulsion in the aqueous phase.
[0015] The temperature control reaction is to control the temperature at 20-40°C for 3-5h. The organic solvent is selected from one or a combination of two or more of methanol, DMSO, DMF, chloroform, tetrahydrofuran, ethyl acetate, ether, and acetone. The amount of the base catalyst is 0.3-0.5wt% of the mass of the arm polyethylene glycol sulfur and the monoolefin epoxy compound, and the base catalyst is selected from one or a combination of two or more of dimethylamine, monoethylamine, diethylamine, isopropylamine, triethylamine, potassium carbonate, sodium carbonate, sodium hydroxide, and potassium hydroxide.
[0016] The alcoholamine early strength agent is selected from one or a combination of two or more of ethanolamine, triethanolamine, diisopropanolamine and triisopropanolamine.
[0017] The aggregate comprises 15-35% of quartz sand with a particle size of 0.01-5 mm, 20-40% of crushed stone with a particle size of 5-10 mm, and 15-35% of crushed stone with a particle size of 10-20 mm.
[0018] The Bayer red mud has a moisture content of 5wt%-20wt%, a particle size of ≤3mm, and Fe 2 O 3 Content ≥50wt%, Na 2 O content ≤ 3wt%.
[0019] The fly ash is selected from one of Class I fly ash and Class II fly ash, or a combination of the two.
[0020] The desulfurized ash is desulfurized ash from a power plant, with a CaO content of 65-85wt%, SO 3 The content is 8-30wt%, and the water content is ≤1wt%.
[0021] The cement strength grade is silicate cement of 42.5-52.5.
[0022] The present invention also provides a method for preparing the red mud-based multi-solid waste water-stabilizing material, comprising the following steps:
[0023] Mix an alcohol amine early strength agent and water to obtain mixture 1; evenly mix mixture 1, Bayer red mud, fly ash, desulfurization ash and cement to obtain mixture 2; evenly mix hyperbranched epoxy resin emulsion and aggregate to obtain mixture 3; evenly mix mixture 2 and mixture 3 to obtain a red mud-based multi-solid wastewater stabilizing material.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] The raw materials of the water-stabilizing material of the present invention contain a self-made hyperbranched epoxy resin emulsion. The terminal epoxy functional group density of the hyperbranched epoxy resin is high. A large number of terminal epoxy groups can chemically react with active groups on the surface of aggregates and cementitious materials to form stable chemical bonds, thereby enhancing the bonding force between aggregates and cementitious materials, reducing the risk of cracking between aggregates and industrial solid waste cementitious materials under the action of water-salt / freeze-thaw cycles, and extending the service life of the water-stabilizing material.
[0026] The present invention realizes the comprehensive recycling of industrial solid waste resources, reduces the cost of road engineering, and effectively prolongs the service life of the road. DETAILED DESCRIPTION
[0027] The present invention will be further described below in conjunction with specific embodiments, but is not limited to the contents of the specification. Unless otherwise specified, the "parts" described in the embodiments of the present invention are all parts by weight. The reagents used are all commercially available reagents in the art.
[0028] Eight-arm polyethylene glycol thiol with weight average molecular weights of 10,000 and 30,000, respectively, were purchased from Shanghai Pengsheng Biotechnology Co., Ltd.
[0029] Four-arm polyethylene glycol thiol with a weight-average molecular weight of 30,000 was purchased from Shanghai Pengsheng Biotechnology Co., Ltd.
[0030] Class I fly ash and Bayer red mud both come from Hebei Wenfeng New Materials Co., Ltd.
[0031] The desulfurization ash from the power plant comes from Hebei Wenfeng New Materials Co., Ltd., with a CaO content of 85wt%, SO 3 The content is 8.8wt%, and the water content is 0.01wt%.
[0032] Example 1
[0033] 1) 0.0125 mol of eight-arm polyethylene glycol thiol with a weight average molecular weight of 30,000, 1.18 g of triethylamine, and 450 g of DMF were mixed evenly, 0.1 mol of glycidyl acrylate was added, and the temperature was controlled at 25° C. to react for 3 h. After the reaction was completed, the organic solvent was evaporated, an appropriate amount of water was added, and shearing and stirring were performed to obtain a hyperbranched epoxy resin emulsion with a concentration of 25 wt%.
[0034] 2) 3 g of diisopropanolamine and 10 g of water are added to obtain mixture 1; mixture 1, 30 g of Bayer red mud, 30 g of grade I fly ash, 4 g of power plant desulfurization ash, and 3 g of 42.5 silicate cement are mixed evenly to obtain mixture 2; 40 g of hyperbranched epoxy resin emulsion and 100 g of aggregate prepared by mixing 30% of quartz sand with a particle size of 0.01-5 mm, 35% of crushed stone with a particle size of 5-10 mm, and 35% of crushed stone with a particle size of 10-20 mm are mixed evenly to obtain mixture 3; mixture 2 and mixture 3 are mixed evenly, and the mixture is allowed to stand for 12 hours to obtain a red mud-based multi-solid waste-based water-stabilizing material.
[0035] Example 2
[0036] The rest is the same as Example 1, except that in step 1), an equimolar amount of eight-arm polyethylene glycol thiol with a weight average molecular weight of 10,000 is used to replace the eight-arm polyethylene glycol thiol with a weight average molecular weight of 30,000.
[0037] Example 3
[0038] The rest is the same as Example 1, except that in step 1), 0.025 mol of four-arm polyethylene glycol thiol with a weight average molecular weight of 30,000 is used to replace the eight-arm polyethylene glycol thiol with a weight average molecular weight of 30,000.
[0039] Example 4
[0040] The rest is the same as Example 1, except that in step 2), the amount of hyperbranched epoxy resin emulsion used is 30 g.
[0041] Example 5
[0042] The rest is the same as Example 1, except that in step 2), the amount of diisopropanolamine used is 2 g.
[0043] Example 6
[0044] The rest is the same as Example 1, except that in step 2), the amount of diisopropanolamine used is 1 g.
[0045] Example 7
[0046] The rest is the same as Example 1, except that in step 2), diisopropanolamine is replaced by triethanolamine of equal mass.
[0047] Example 8
[0048] 1) 0.0125 mol of eight-arm polyethylene glycol thiol with a weight average molecular weight of 30,000, 1.18 g of triethylamine, and 450 g of DMF were mixed evenly, 0.11 mol of glycidyl acrylate was added, and the temperature was controlled at 25° C. to react for 3 h. After the reaction was completed, the organic solvent was evaporated, an appropriate amount of water was added, and shearing and stirring were performed to obtain a hyperbranched epoxy resin emulsion with a concentration of 20 wt%.
[0049] 2) 3 g of diisopropanolamine and 10 g of water are added to obtain mixture 1; mixture 1, 30 g of Bayer red mud, 15 g of grade I fly ash, 4 g of power plant desulfurization ash, and 5 g of 42.5 silicate cement are mixed evenly to obtain mixture 2; 40 g of hyperbranched epoxy resin emulsion and 100 g of aggregate prepared by mixing 25% of quartz sand with a particle size of 0.01-5 mm, 40% of crushed stone with a particle size of 5-10 mm, and 35% of crushed stone with a particle size of 10-20 mm are mixed evenly to obtain mixture 3; mixture 2 and mixture 3 are mixed evenly, and the mixture is allowed to stand for 12 hours to obtain a red mud-based multi-solid wastewater stabilizing material.
[0050] Comparative Example 1
[0051] The rest is the same as Example 1, except that in step 2), an equal mass of carboxylate early strength agent calcium formate is used to replace triethanolamine.
[0052] Comparative Example 2
[0053] The rest is the same as Example 1, except that in step 2), no hyperbranched polyepoxy resin emulsion is added and the amount of water used is 40 g.
[0054] The water-stable materials prepared in the above examples and comparative examples were subjected to the following performance tests:
[0055] Unconfined compressive strength test: Prepare Ø150mm×150mm specimens, and after forming, cure them in a constant temperature and humidity curing box at a temperature of 20±1℃ and a relative humidity of 95±1% to an appropriate age. Refer to T0805-1994 in the "Test Procedure for Stabilized Materials of Inorganic Binders for Highway Engineering", and use a press to measure the unconfined compressive strength of the specimens at two different ages of 7 days and 28 days.
[0056] Water-salt / freeze-thaw cycle effect: The specimens after curing for 28 days were immersed in 8wt% sodium sulfate solution, and then placed in a freeze-thaw device for 50 freeze-thaw cycles. One cycle included: dropping from 10℃ to -25℃ for 4h, maintaining a constant temperature at -25℃ for 4h, rising from -25℃ to 10℃ for 2h, maintaining a constant temperature at 10℃ for 2h, and then retesting the unconfined compressive strength, and calculating the strength loss rate.
[0057] Toxicity leaching rate of heavy metals: refer to the methods and steps of "Horizontal Oscillation Method for Toxicity Leaching of Solid Waste" (HJ 557-2009), and use inductively coupled plasma mass spectrometer (ICP-MS) to determine the harmful ion content in the leaching solution.
[0058] Table 1 Performance test results
[0059]
[0060]
[0061] Table 2 Performance test results
[0062]
[0063] It can be seen from Table 1 that the water-stable material prepared by the present invention has excellent resistance to water-salt / freeze-thaw cycles.
[0064] It can be seen from the heavy metal leaching rate test results of Example 1, Examples 5-7 and Comparative Examples in Table 2 that the alcohol amine early strength agent has an obvious effect of synergizing with the hyperbranched epoxy resin to reduce the leaching rate of heavy metal ions.
[0065] The above detailed description is a specific description of one feasible embodiment of the present invention. The embodiment is not intended to limit the patent scope of the present invention. Any equivalent implementation or modification that does not deviate from the present invention should be included in the scope of the technical solution of the present invention.
Claims
1. A red mud-based multi-solid wastewater stabilizing material with improved weather resistance, characterized in that: The invention comprises the following raw materials in parts by weight: 15-30 parts of Bayer red mud, 15-30 parts of fly ash, 2.5-4 parts of desulfurized ash, 3-5 parts of cement, 80-100 parts of aggregate, 30-40 parts of hyperbranched epoxy resin emulsion, 1-3 parts of alcoholamine early strength agent and 5-15 parts of water; the hyperbranched epoxy resin emulsion is prepared by Michael addition reaction of multi-arm polyethylene glycol thiol and monoolefin epoxy compound at a molar ratio of thiol to olefin of 1:1-1.
1.
2. The red mud-based multi-solid wastewater stabilizing material with improved weather resistance according to claim 1, characterized in that: The multi-arm polyethylene glycol thiol has a weight average molecular weight of 10,000-30,000 and is selected from one or a combination of two or more of four-arm polyethylene glycol thiol, six-arm polyethylene glycol thiol, and eight-arm polyethylene glycol thiol; preferably eight-arm polyethylene glycol thiol.
3. The red mud-based multi-solid wastewater stabilizing material with improved weather resistance according to claim 1, characterized in that: The monoolefin epoxy compound is selected from one or a combination of two or more of 3,4-epoxycyclohexyl methyl methacrylate, (3,4-epoxycyclohexyl) methyl acrylate, glycidyl acrylate, glycidyl methacrylate, and 4-hydroxybutyl acrylate glycidyl ether.
4. The red mud-based multi-solid wastewater stabilizing material with improved weather resistance according to claim 1, characterized in that: The hyperbranched epoxy resin emulsion has a solid content of 18-25%.
5. The red mud-based multi-solid wastewater stabilizing material with improved weather resistance according to claim 1, characterized in that: The hyperbranched epoxy resin emulsion is prepared by a method comprising the following steps: The multi-arm polyethylene glycol sulfur, the base catalyst and the organic solvent are uniformly mixed, and the monoolefin epoxy compound is added to control the temperature for reaction. After the reaction is completed, the organic solvent is evaporated, and water is added, and shearing and stirring are performed to obtain a hyperbranched epoxy resin emulsion.
6. The red mud-based multi-solid wastewater stabilizing material with improved weather resistance according to claim 1, characterized in that: The temperature-controlled reaction is to control the temperature at 20-40°C for 3-5 hours; the organic solvent is selected from one or a combination of two or more of methanol, DMSO, DMF, chloroform, tetrahydrofuran, ethyl acetate, ether, and acetone; the amount of the base catalyst is 0.3-0.5wt% of the sum of the mass of the arm polyethylene glycol sulfur and the monoolefin epoxy compound, and the base catalyst is selected from one or a combination of two or more of dimethylamine, monoethylamine, diethylamine, isopropylamine, triethylamine, potassium carbonate, sodium carbonate, sodium hydroxide, and potassium hydroxide.
7. The red mud-based multi-solid wastewater stabilizing material with improved weather resistance according to claim 1, characterized in that: The alcoholamine early strength agent is selected from one or a combination of two or more of ethanolamine, triethanolamine, diisopropanolamine and triisopropanolamine.
8. The red mud-based multi-solid wastewater stabilizing material with improved weather resistance according to claim 1, characterized in that: The aggregate comprises 15-35% of quartz sand with a particle size of 0.01-5 mm, 20-40% of crushed stone with a particle size of 5-10 mm, and 15-35% of crushed stone with a particle size of 10-20 mm.
9. The red mud-based multi-solid wastewater stabilizing material with improved weather resistance according to claim 1, characterized in that: The fly ash is selected from one of Class I fly ash and Class II fly ash or a combination of the two; the desulfurization ash is desulfurization ash from a power plant, with a CaO content of 65-85wt%, a SO3 content of 8-30wt%, and a moisture content of ≤1wt%; the Bayer process red mud has a moisture content of 5wt%-20wt%, a particle size of ≤3mm, a Fe2O3 content of ≥50wt%, and a Na2O content of ≤3wt%.
10. The method for preparing the red mud-based multi-solid waste water-stabilizing material according to any one of claims 1 to 9, characterized in that: The steps include: Mix an alcohol amine early strength agent and water to obtain mixture 1; evenly mix mixture 1, Bayer red mud, fly ash, desulfurization ash and cement to obtain mixture 2; evenly mix hyperbranched epoxy resin emulsion and aggregate to obtain mixture 3; evenly mix mixture 2 and mixture 3 to obtain a red mud-based multi-solid wastewater stabilizing material.
Citation Information
Patent Citations
Road material for producing red mud by using Bayer process
CN101671986B
A crack-resistant water-stabilized layer material for roads containing electrolytic manganese slag and its preparation method
CN110423085B
A crack-resistant and settlement-resistant road water-stabilized layer material and its preparation method
CN113698164B
Normal-temperature curing adhesive for repairing EPDM (Ethylene-Propylene-Diene Monomer) heat
CN114921208A
Red mud-based cementing material, red mud-based lightweight aggregate, red mud-based lightweight aggregate concrete and preparation method therefor
WO2022142137A1